Flexible Wearables for Plants (Small 50/2021) - Qu, Chun‐Chun; Sun, Xu‐Yang; Sun, Wen‐Xiu; Cao, Ling‐Xiao; Wang, Xi‐Qing; He, Zhi‐Zhu (Small (Weinheim an der Bergstrasse, Germany), 2021)
Flexible Wearables for Plants Recent research progress in flexible wearables for plants is comprehensively reviewed by Xi‐Qing Wang, Zhi‐Zhu He, and co‐workers in article number 2104482. The emerging applications of flexible plant wearables, including physiological indicators, surrounding environment, crop quality, and active control of growth, are highlighted. The future opportunities and challenges of plant wearables are also discussed in detail.